Crimes of the Holocaust : The Law Confronts Hard Cases - Landsman, Stephan (Book collections on Project MUSE., 2005)
"In Crimes of the Holocaust, Stephan Landsman provides detailed analyses of the International Military Tribunal prosecution at Nuremberg in 1945, the Eichmann trial in Israel in 1961, the 1986 Demjanjuk trial in Israel, and the 1990 prosecution of Imre Finta in Canada. Landsman presents each case and elaborates the difficulties inherent in achieving both a fair trial and a measure of justice in the aftermath of heinous crimes." "Meticulously combing through volumes of testimony and documentary information about each case, Landsman offers judicious and critical assessments of the proceedings. He levels pointed criticism at numerous elements of this relatively recent judicial invention, sparing neither judges nor counsel and remaining keenly aware of the human implications. Deftly weaving legal analysis with cultural context, Landsman offers the first rigorous examination of these problematic proceedings and proposes guideposts for contemporary tribunals. Crimes of the Holocaust is an authoritative account of the Gordian knot of genocide prosecution in world courts, which will persist as a confounding issue as we are faced with a trial of Saddam Hussein. This volume will be compelling reading for legal scholars as well as laypersons interested in these cases and the issues they address."--Jacket